Efficacy and safety of drug-eluting stent for the intracranial atherosclerotic disease: A systematic review and meta-analysis. (January 2019) - Ye, Gengfan; Yin, Xiaoliang; Yang, Ximeng; Wang, Junjie; Qi, Peng; Lu, Jun; Wang, Lijun; Wang, Daming
Highlights: ICAD is one of the most common causes of stroke worldwide, especially among Asians. Endovascular DES for sICAD can effectively reduce the risk of ISR. Higher preoperative stenosis rate implies higher perioperative complications risk. The complication rate is acceptable compared with SAMMPRIS and VISSIT trials. Abstract: Drug-eluting stent (DES) is a potential endovascular treatment for patients with symptomatic intracranial atherosclerotic disease (sICAD). However, evidence regarding the treatment of ICAD with DES is lacking. We systematically searched Pubmed, Embase, Cochrane database (before 2017-12-21) for literature reporting the application of DES in the treatment of sICAD. The main outcomes were as follows: the incidence of any stroke or death within 30 days (perioperative complications), ischemic stroke in the territory of the qualifying artery beyond 30 days (long-term complications), in-stent restenosis rate (ISR) and symptomatic ISR during follow-up. Those studies with mean stenosis rate greater than 70% and less than 70% were defined as severe and moderate stenosis group, respectively. The random effect model was used to pool the data. Of 518 articles, 13 studies were eligible and included in our analysis (N = 336 patients with 364 lesions). After the implantation of DES, perioperative complications (mortality = 0) occurred in 6.0% (95%CI 2.0%–11.9%), long-term complications occurred in 2.2% (95%CI 0.7%–4.5%), ISR rate was 4.1% (95%CI 1.6%–7.7%) and the symptomatic ISR rate was only 0.5% (95%CI 0–2.2%). In addition, subgroup analysis showed that the perioperative complication rate in severe stenosis group [10.6% (95%CI 6.5%–15.7%)] was significantly (p < 0.01) higher than that in moderate stenosis group [1.0% (95%CI 0.3%–3.5%)]. In summary, endovascular DES implantation is a relatively safe and effective method compared with stents or medical management group in SAMMPRIS and VISSIT trials. However, a higher preoperative stenosis rate may imply a higher risk of perioperative complications. Further studies are needed.